2021
DOI: 10.4097/kja.21020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of endotracheal intubation-related judicial precedents in South Korea

Abstract: This article has been accepted for publication and has undergone full peer review but has notbeen through the copyediting, typesetting, pagination, and proofreading processes, which may lead to differences between this version and the version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Additionally, a closed claim analysis in Korea showed that 58.7% of cases of airway-related malpractice lawsuits were from nonperioperative areas and that 81% of cases resulted in payments for the claims. 13 Anesthesiologists and anesthesia groups take on a significant liability risk by responding to airway pages and in serving as the immediately available, on-location hospital airway experts.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a closed claim analysis in Korea showed that 58.7% of cases of airway-related malpractice lawsuits were from nonperioperative areas and that 81% of cases resulted in payments for the claims. 13 Anesthesiologists and anesthesia groups take on a significant liability risk by responding to airway pages and in serving as the immediately available, on-location hospital airway experts.…”
Section: Discussionmentioning
confidence: 99%
“…This study updated the data regarding critical incidents associated with pediatric anesthesia at a single tertiary teaching children's hospital in 2014-2019, and compared it 12) Pharmacological (n = 1) Medication error 0 (0) 1 (4) 1 (4) Cardiogenic shock (1) Total cardiac arrest (n = 25) 7 (28) 18 (72) 25 (100) Values are presented as number (%). PALS: pediatric advanced life support.…”
Section: Discussionmentioning
confidence: 99%
“…Second, education program should be further strengthened, especially at the beginning of each training year. Bringing attention to frequently occurring accidents as well as recognizing of complications will reduce the chances of the same events occurring again [ 18 ]. Third, it is also important to maintain constant resources and interest in what is well maintained in terms of quality management.…”
Section: Discussionmentioning
confidence: 99%
“…Because this study was performed to analyze HICS effectiveness via actual measurements, it focused on an area in which HICS had been applied. The study area was located in Jangyu Mugye-dong, Gimhae-si, Gyeongsangnam-do, where the Ministry of Environment of the Republic of Korea has implemented a project to prevent heatwaves as a climate change adaptation measure [37]. Trees and vegetation, green roofs, cool pavements, and cool roofs have been established in the region as HICS.…”
Section: Study Area and Analysis Targetsmentioning
confidence: 99%